Primary Roles of Branched Chain Amino Acids (BCAAs) and Their Metabolism in Physiology and Metabolic Disorders - Tomoki Bo; Junichi Fujii (Molecules)
Leucine, isoleucine, and valine are collectively known as branched chain amino acids (BCAAs) and are often discussed in the same physiological and pathological situations. The two consecutive initial reactions of BCAA catabolism are catalyzed by the common enzymes referred to as branched chain aminotransferase (BCAT) and branched chain α-keto acid dehydrogenase (BCKDH). BCAT transfers the amino group of BCAAs to 2-ketoglutarate, which results in corresponding branched chain 2-keto acids (BCKAs) and glutamate. BCKDH performs an oxidative decarboxylation of BCKAs, which produces their coenzyme A-conjugates and NADH. BCAT2 in skeletal muscle dominantly catalyzes the transamination of BCAAs. Low BCAT activity in the liver reduces the metabolization of BCAAs, but the abundant presence of BCKDH promotes the metabolism of muscle-derived BCKAs, which leads to the production of glucose and ketone bodies. While mutations in the genes responsible for BCAA catabolism are involved in rare inherited disorders, an aberrant regulation of their enzymatic activities is associated with major metabolic disorders such as diabetes, cardiovascular disease, and cancer. Therefore, an understanding of the regulatory process of metabolic enzymes, as well as the functions of the BCAAs and their metabolites, make a significant contribution to our health.